A practical method of bandaging the fingers - (:unkn) unknown (SPRINGER VERLAG, 1996)
It is difficult to secure dressings and exert pressure on fingers which have incisions or skin grafts on them. A method that has been found to be extremely useful over the first few days is described.
Keywords: fingers; injury; surgical gloves